2008
DOI: 10.1080/15374410801955771
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Impairment Among Adolescents Engaging in Different Types of Deliberate Self-Harm

Abstract: This retrospective chart review study of 227 participants examined the psychiatric profiles of outpatient adolescents ages 12 to 19 years (M = 15.08 years, SD = 1.72 years) engaging in different types of deliberate self-harm (DSH) behaviors. Participants were divided into four groups: no deliberate self-harm (NoDSH; n = 119), nonsuicidal self-injury only (NSSI only; n = 30), suicide attempt only (n = 38), and suicide attempt plus NSSI (n = 40). Those who attempted suicide were more likely to have major depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
274
2
19

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(318 citation statements)
references
References 25 publications
20
274
2
19
Order By: Relevance
“…This is consistent with another psychological autopsy study, which also reported a large proportion of PDs among suicide completers; notably the investigators found that borderline PD was present in 33% of the cases (132). PD during adolescence is also associated with non-suicidal selfinjurious behavior such as cutting and burning (133)(134)(135).…”
Section: Adverse Outcomes and Adaptive Functioningsupporting
confidence: 78%
“…This is consistent with another psychological autopsy study, which also reported a large proportion of PDs among suicide completers; notably the investigators found that borderline PD was present in 33% of the cases (132). PD during adolescence is also associated with non-suicidal selfinjurious behavior such as cutting and burning (133)(134)(135).…”
Section: Adverse Outcomes and Adaptive Functioningsupporting
confidence: 78%
“…2 Research with clinical samples shows even higher rates of ∌40%. 5 Engaging in NSSI is a risk factor for suicidal thoughts and behaviors and a precursor to more serious psychopathology. 6 In fact, as publication of the new Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-V) approaches, it seems likely that NSSI will become a new psychiatric diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…According Nock (2009), adolescents may exhibit NSSI to cope with elevated levels of general psychological distress, conceptualized as a wide variety of psychological symptoms (Jacobson, Muehlenkamp, Miller, & Turner, 2008;Nock, Joiner, Gordon, Lloyd-Richardson, & Prinstein, 2006) including both elevated rates of internalizing (e.g., anxiety, depression; e.g., Andover, Pepper, Ryabchencko, Orrico, & Gibb, 2005) and externalizing symptoms (e.g., conduct behavioral problems; e.g., Baetens, Claes, Muehlenkamp, Grietens, & Onghena, 2012;Brunner, Parzer, Haffner, Steen, & Roos, 2007). In line with Baetens et al (2012) and Klonsky and Olino (2008), it has been suggested that NSSI in community adolescents is a reflection of a general psychological distress and is not always accompanied by a diagnosable psychopathological condition.…”
Section: Intrapersonal Correlates Of Nssimentioning
confidence: 99%